Public support for innovation: A systematic review of the literature and implications for open innovation - Jugend, Daniel [UNESP]; Fiorini, Paula De Camargo; Armellini, Fabiano; Ferrari, Aline Gabriela [UNESP] (Elsevier, 2020)
Although public support for innovation is one of the main contemporary topics in innovation management and even economic and industrial development, there are no recent studies that have consolidated and analyzed the publications on the topic, especially from the perspective of open innovation (OI). Therefore, the objective of this article is to contribute to the field by assessing what types of public practices for innovation comprise the term public support for innovation'' and its relationship with OI. To achieve these objectives, we conducted a systematic review and qualitative analysis of 121 articles. Our results reveal that (i) the use of the term public support for innovation'' is emerging in innovation management and innovation policies; (ii) there are differences in research approaches that focus on innovation policy'' and public support for innovation''; and (iii) the OI is used more than management theories to analyze public support for innovation. Furthermore, our results indicate that public support for innovation can be analyzed from four dimensions: (i) financial support for R&D activities; (ii) development through innovation; (iii) support for sectorial programs; and (iv) university–industry–government collaboration (triple helix).
Keywords: Innovation policy; Public policy; Public support for innovation; Systematic literature review